Tread rubber composition, preparation method thereof and tire
By using oxidized nanocarbon ball composite materials as fillers in rubber, combined with specific processes and additives, the problem of insufficient performance of rubber materials in friction and wear is solved, significantly improving wear resistance and reinforcement, and extending the use of tires Lifespan and reduce fuel consumption.
Patent Information
- Application Number
- CN202411416355.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing rubber materials have insufficient performance in friction and wear, especially the poor bonding interface between oxidized nanocarbon balls and rubber, which affects their application as reinforcement fillers.
Using oxidized nanocarbon ball composite materials as filler, it is prepared by mixing with natural rubber, carbon black and white carbon black to improve the wear resistance of rubber and reduce compression and heat generation, and through specific process steps and additive combinations, it improves the Overall performance of rubber.
It significantly improves the wear resistance and reinforcement of rubber, reduces compression and heat generation, extends the service life of the tire and reduces fuel consumption.
Smart Images

Figure CN119144057A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tire rubber manufacturing, in particular to a tread rubber composition and a preparation method thereof and a tire. Background Art
[0002] Rubber composite materials such as tires and conveyor belts will inevitably be affected by rolling friction and sliding friction during use. Wear resistance is an important property of rubber products that cannot be ignored. Tires, as the rubber products with the largest consumption, are particularly valued for their wear resistance. The wear resistance of tires affects the service life of tires and the generation of rubber debris. Rubber debris is an important source of air pollutants. Therefore, studying rubber wear is of great significance to the production and application of rubber products.
[0003] In recent years, researchers have explored the performance of carbon nanomaterials such as graphite, carbon nanotubes and graphene in rubber, and the results show that they perform well in the field of friction and wear. Oxidized nanocarbon spheres, which are allotropes of graphite, carbon nanotubes and graphene, are expected to become solid lubricants and anti-wear agents with better performance. They have low Payne effect and low rolling resistance effect that traditional carbon black does not have, so they have great application prospects in rubber. However, the bonding interface between oxidized nanocarbon spheres and rubber is relatively poor.
[0004] In view of this, how to make oxidized nanocarbon spheres into fillers with the same reinforcing properties as traditional fillers and apply them to rubber will be a very promising direction. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a tread rubber composition, to which an oxidized nano-carbon ball composite material is added. The composite material is prepared by mixing oxidized nano-carbon balls, and can serve as a reinforcing filler while improving the wear resistance of the rubber and reducing the compression heat generated by the rubber.
[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions: A tread rubber composition, the rubber composition is prepared by mixing the following raw materials in parts by weight: 100 parts of natural rubber, Carbon black 20-50 parts, 20-30 parts of white carbon black, 4-16 parts of oxidized nano carbon ball composite material, 10-20 parts of rubber operating oil, Silane coupling agent 2-8 parts, Petroleum resin 2-2.5 parts, And appropriate amounts of vulcanizing agent, antioxidant, activator, accelerator and microcrystalline wax; The oxidized nano-carbon sphere composite material is prepared by mixing the following raw materials in parts by weight: 20-40 parts of natural rubber, 1-10 parts of carbon black, 5-15 parts of oxidized nano carbon spheres; The carbon black particle size is 20-40nm; The white carbon black is prepared by a precipitation method and has a BET specific surface area of 100-200 m 2 / g.
[0007] Preferably, the rubber composition is prepared by mixing the following raw materials in parts by weight: 100 parts of natural rubber, Carbon black 20-50 parts, 20-30 parts of white carbon black, 14-16 parts of oxidized nano carbon ball composite material, 10-20 parts of rubber operating oil, Silane coupling agent 2-8 parts, Petroleum resin 2-2.5 parts, Anti-aging agent 0.5-1.5 parts, 1-2 parts of microcrystalline wax, 4-6 parts of active agent, 2-5 parts of accelerator, Sulfur 1-5 parts.
[0008] Preferably, the method for preparing the oxidized nano-carbon ball composite material comprises the following steps: starting an internal mixer, setting the speed to 30-45 rpm, adding natural rubber and carbon black, mixing for 20-35 seconds, adding oxidized nano-carbon balls, continuing to mix for 1-2 minutes, debonding, and obtaining the oxidized nano-carbon ball composite material.
[0009] Preferably, the active agent is zinc oxide and stearic acid: zinc oxide is 1.0-4.0 parts, and stearic acid is 1.0-3.0 parts.
[0010] Preferably, the accelerators include accelerator DPG, accelerator DM and accelerator CZ: accelerator DPG is 0.1-2.0, accelerator DM is 0.2-2.0 parts, and accelerator CZ is 0.2-2.0 parts.
[0011] Furthermore, the present invention also discloses a method for preparing the rubber composition, comprising the following steps: 1) One-stage mixing: Mixing is carried out using an internal mixer; natural rubber is added, and the pressing mass is pressed down and held for 55-65 seconds; the pressing mass is raised, and white carbon black, 35%-45% carbon black, oxidized nano-carbon ball composite materials, silane coupling agent, petroleum resin, microcrystalline wax, activator and antioxidant are added, and the pressing mass is pressed down and held for 55-65 seconds; the pressing mass is raised, and 55%-65% carbon black and rubber operating oil are added, and the pressing mass is pressed down and held for 80-100 seconds; the pressing mass is raised and cleaned; 2) Second stage mixing: Use open mill for mixing; discharge rubber to open mill, adjust the roller distance of double roll open mill to 0.8-1.2mm, so that the rubber compound after mixing is wrapped around the roller; add accelerator and vulcanizer in sequence, cut the left and right knives three times each; make triangle wrapping five times when the roller is 0.15-0.25mm; adjust the roller distance to 1.5-2.0mm, unload the sheet, and park.
[0012] Furthermore, the present invention also discloses a tire, which includes a tread, and the tread is prepared by vulcanizing the rubber composition according to any one of claims 1 to 6.
[0013] The beneficial effects of the present invention are as follows: the interface bonding between the oxidized nano-carbon ball composite material and the rubber is better than that of the oxidized nano-carbon balls. The present invention uses precipitated silica, carbon black and the oxidized nano-carbon ball composite material as reinforcing fillers, and has high reinforcement. With the increase of the oxidized nano-carbon ball composite material, the filler reinforcement is significantly improved. At the same time, the rubber composition has high wear resistance, especially the compression heat generation is significantly reduced, which is beneficial to reducing fuel consumption and increasing the service life of the tire.
[0014] In the rubber composition of the present invention, in addition to the above-mentioned components, different additives can be mixed, such as other fillers commonly used in tires and other rubber compositions, vulcanizing agents, vulcanization accelerators, different types of oils, antioxidants, plasticizers, etc. These additives are mixed in a common way to obtain a rubber composition that can be used for vulcanization. The amount of these additives can also be a conventional, usually mixed amount, provided that the purpose of the present invention is not adversely affected. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Scanning electron microscope images of oxidized nano-carbon ball composite materials, (a) 50,000 times, (b) 100,000 times.
[0016] Figure 2 These are scanning electron microscope images of cross-sections of vulcanized rubbers of composite materials with oxidized nano-carbon balls in different proportions, (a), (b), (C), (d) at 50,000 times, (e), (f), (g), (h) at 100,000 times, (a) and (e) are Example 1, (b) and (f) are Example 2, (C) and (g) are Example 3, and (d) and (h) are Comparative Example 5. DETAILED DESCRIPTION
[0017] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The formulas of the embodiments and comparative examples are shown in Table 1 (parts by weight), and the formula of the oxidized nano-carbon sphere composite material is shown in Table 2 (parts by weight).
[0019] The preparation methods of Examples 1-3 and Comparative Example 5 are as follows: 1) One-stage mixing: Mixing is carried out using an internal mixer; natural rubber is added, and the pressing mass is pressed down and held for 60 seconds; the pressing mass is raised, and white carbon black, 40% carbon black, oxidized nano-carbon ball composite material, silane coupling agent, petroleum resin, microcrystalline wax, activator and antioxidant are added, and the pressing mass is pressed down and held for 60 seconds; the pressing mass is raised, and 60% carbon black and rubber operating oil are added, and the pressing mass is pressed down and held for 90 seconds; the pressing mass is raised and cleaned; 2) Second stage mixing: Use open mill for mixing; discharge rubber to open mill, adjust the roller distance of double-roll open mill to 1.0mm, so that the rubber compound after mixing is wrapped around the roller; add accelerator and vulcanizer in sequence, cut the left and right knives three times each; make triangle wrapping passes five times when the roller is 0.20mm; adjust the roller distance to 1.5mm, unload the sheet, and park.
[0020] The preparation methods of Comparative Examples 1-4 refer to the examples.
[0021] The preparation method of the oxidized nano-carbon ball composite material is as follows: start the internal mixer, set the speed to 30-45 rpm, add natural rubber and carbon black, mix for 20-35 seconds, add the oxidized nano-carbon balls, continue mixing for 1-2 minutes, remove the glue, and obtain the oxidized nano-carbon ball composite material.
[0022] Table 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Example 1 Example 2 Example 3 Natural rubber*1 100 100 100 100 100 100 100 100 Carbon black*2 45 50 40 40 40 40 40 40 White carbon black*3 25 10 25 25 25 25 25 25 Oxidized nanocarbon sphere composites / / / / 20 5 10 15 Oxidized nanocarbon spheres*4 / / 0.6 5 / / / / Rubber operating oil*5 15 15 15 15 15 15 15 15 Stearic acid*6 2 2 2 2 2 2 2 2 Anti-aging agent*7 1 1 1 1 1 1 1 1 Silane coupling agent*8 4 2 4 4 4 4 4 4 Resin*9 2.13 2.13 2.13 2.13 2.13 2.13 2.13 2.13 Zinc oxide*10 3 3 3 3 3 3 3 3 Paraffin*11 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 Accelerator*12 1 1 1 1 1 1 1 1 Accelerator*13 1 1 1 1 1 1 1 1 Accelerator*14 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Oil-filled sulfur*15 2 2 2 2 2 2 2 2 total 203.13 191.13 198.73 203.13 218.13 203.13 208.13 213.13 Table 2 Example 1 Example 2 Example 3 Comparative Example 5 Natural rubber*1 100 100 100 100 Carbon black*2 10 10 10 10 Oxidized nanocarbon spheres*4 5 10 15 15 Table 1, 2 Footnotes *1: SCR20, a product of Hainan Sinochem; *2: N234, Cabot Chemicals; *3: 1165MP, Solvay Fine Chemical Additives (Qingdao) Co., Ltd.; *4: Oxidized nanocarbon spheres, Zibo Yideye New Material Technology Co., Ltd.; *5: V500, product of Ningbo Hansheng Co., Ltd. *6: Stearic acid, a product of Yihai Kerry; *7: Antioxidant 4020 (6PPD), a product of Sinopec Nanjing Chemical Industry Co., Ltd.; *8: Si69, Evonik Chemical Products; *9: C5 / C9 resin, ExxonMobil product; *10: Zinc oxide, product of Qingdao Haiyan Chemical Co., Ltd.; *11: Microcrystalline wax, a product of Yanggu Huatai; *12: Accelerator DPG (D), a product of Shandong Shangshun Chemical Co., Ltd.; *13: Accelerator DM, a product of Shandong Shangshun Chemical Co., Ltd.; *14: Feeding agent CBS (CZ), a product of Shandong Shangshun Chemical Co., Ltd.; *15: Oil-filled sulfur powder, a product of Wuxi Huasheng Rubber New Material Technology Co., Ltd.
[0023] The rubber compositions obtained in the examples and comparative examples were subjected to performance tests, and the test results are shown in Table 3.
[0024] The test method is as follows: 1) Vulcanization characteristics: According to GB / T 9869-1997 standard, the UR-2030 rotorless vulcanizer produced by Taiwan Uni-Con Company was used to measure the vulcanization curve and vulcanization characteristic parameters at 143°C and a swing angle of 1°.
[0025] 2) Tensile properties: The tensile strength and tear strength of the rubber composition are in accordance with GB / T 528-2009 and GB / T 529-2008 standards. The tensile specimen is dumbbell-shaped and the tear specimen is right-angled. The test is performed using a U-CAN UT-2060 electronic tensile testing machine at a rate of 500 mm / min.
[0026] 3) Abrasion test: According to GB / T 1689-1998 standard, the wear amount of the material is tested using the GOTECH GT-7012-A Akron abraser produced by the High Speed Rail Company.
[0027] 4) Heat generation performance: The compression fatigue heat generation performance of the material was tested in accordance with GB / T 15584-1995 standard. The testing instrument was U-CAN UD-3801 compression fatigue heating testing machine. The testing conditions were frequency 30Hz, strain double amplitude 5.71mm, load force 24.5Kg, test time 25min, and the test specimen was a cylinder with a height of 25mm and a diameter of 17.8mm.
[0028] Table 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Example 1 Example 2 Example 3 T90(min) 100 72 86 91 110 94 96 99 TB(MPa) 100 90 85 99 100 101 106 108 M300(MPa) 100 94 73 79 98 87 93 99 EB(%) 100 94 108 102 109 101 98 101 <![CDATA[Akron abrasion (cm 3 / 1.61 km)]]> 100 104 105 104 96 102 98 90 Compression heat (℃) 100 99 99 98 88 95 92 89 Analyzing Table 3, Example 3 is the best example with the best comprehensive performance. It can be seen that after adding the oxidized nano-carbon ball composite material, Example 3 has higher strength and high wear resistance, especially significantly reduced compression heat generation, which is beneficial to reducing fuel consumption and increasing service life of the tire.
[0029] However, with the increase of the amount of oxidized nanocarbon spheres, the aggregates of the dumbbell-shaped specimen cross section become larger and the number of aggregates increases. This shows that the more the amount of oxidized nanocarbon spheres composite material is used, the more difficult it is to disperse in the rubber matrix, and too much is not conducive to the performance of the rubber.
[0030] The above is a description of the embodiments of the present invention. Through the above description of the disclosed embodiments, professionals and technicians in the field can implement or use the present invention. Various modifications to these embodiments will be apparent to professionals and technicians in the field. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown in this article, but will conform to the widest range consistent with the principles and novelties disclosed herein.
Claims
1. A tread rubber composition, characterized in that: The rubber composition is prepared by mixing the following raw materials in parts by weight: 100 parts of natural rubber, Carbon black 20-50 parts, 20-30 parts of white carbon black, 4-16 parts of oxidized nano carbon ball composite material, 10-20 parts of rubber operating oil, Silane coupling agent 2-8 parts, Petroleum resin 2-2.5 parts, And appropriate amounts of vulcanizing agent, antioxidant, activator, accelerator and microcrystalline wax; The oxidized nano-carbon sphere composite material is prepared by mixing the following raw materials in parts by weight: 20-40 parts of natural rubber, 1-10 parts of carbon black, 5-15 parts of oxidized nano carbon spheres; The carbon black particle size is 20-40nm; The white carbon black is prepared by a precipitation method, and has a BET specific surface area of 100-200 m 2 / g.
2. The rubber composition according to claim 1, characterized in that The rubber composition is prepared by mixing the following raw materials in parts by weight: 100 parts of natural rubber, Carbon black 20-50 parts, 20-30 parts of white carbon black, 14-16 parts of oxidized nano carbon ball composite material, 10-20 parts of rubber operating oil, Silane coupling agent 2-8 parts, Petroleum resin 2-2.5 parts, Anti-aging agent 0.5-1.5 parts, 1-2 parts of microcrystalline wax, 4-6 parts of active agent, 2-5 parts of accelerator, Sulfur 1-5 parts.
3. The rubber composition according to claim 1 or 2, characterized in that: The preparation method of the oxidized nano-carbon ball composite material comprises the following steps: starting an internal mixer, setting the speed to 30-45 revolutions, adding natural rubber and carbon black, mixing for 20-35 seconds, adding oxidized nano-carbon balls, continuing mixing for 1-2 minutes, debonding, and obtaining the oxidized nano-carbon ball composite material.
4. The rubber composition according to claim 1 or 2, characterized in that: The active agent is zinc oxide and stearic acid: the zinc oxide is 1.0-4.0 parts, and the stearic acid is 1.0-3.0 parts.
5. The rubber composition according to claim 1 or 2, characterized in that: The accelerators include accelerator DPG, accelerator DM and accelerator CZ: accelerator DPG is 0.1-2.0, accelerator DM is 0.2-2.0 parts, and accelerator CZ is 0.2-2.0 parts.
6. The method for preparing the rubber composition according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) One-stage mixing: Mixing is carried out using an internal mixer; natural rubber is added, and the pressing mass is pressed down and held for 55-65 seconds; the pressing mass is raised, and white carbon black, 35%-45% carbon black, oxidized nano-carbon ball composite materials, silane coupling agent, petroleum resin, microcrystalline wax, activator and antioxidant are added, and the pressing mass is pressed down and held for 55-65 seconds; the pressing mass is raised, and 55%-65% carbon black and rubber operating oil are added, and the pressing mass is pressed down and held for 80-100 seconds; the pressing mass is raised and cleaned; 2) Second stage mixing: Use open mill for mixing; discharge rubber to open mill, adjust the roller distance of double roll open mill to 0.8-1.2mm, so that the rubber compound after mixing is wrapped around the roller; add accelerator and vulcanizer in sequence, cut the left and right knives three times each; make triangle wrapping five times when the roller is 0.15-0.25mm; adjust the roller distance to 1.5-2.0mm, unload the sheet, and park.
7. A tire, characterized in that: The tire comprises a tread, and the tread is prepared by vulcanizing the rubber composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Carbon oxide nano onion / polybutadiene-polystyrene-vinylpyridine composite material as well as preparation method and application thereof
CN114790305A
Anti-static Teflon conveying belt and preparation process thereof
CN117645090A
Tire tread rubber composition with good wet tractionproperty
KR1020070027187A
Rubber reinforced with fillers dispersed in functionalized silsesquioxanes
US20170088696A1
